Measurement invariance of the self-care Scale for older people in Costa Rica and Spain. Issue 3 (4th March 2023) - Tomás, José M.; Sancho, Patricia; Blanco-Molina, Mauricio; Pinazo-Hernandis, Sacramento
ABSTRACT: Successful aging is closely related to self-care behaviors. In fact, self-care is one of the most important aspects of a healthy life. It is in this context that the Self-Care Scale for the Older People appears. The main aim of this study is to offer evidence on the measurement invariance of the scale in samples of older adults from countries with cultural differences, specifically Costa Rica and Spain. The research approach is a panel design of 272 Costa Rican older adults and 1166 Spanish older adults. Statistical analyses considered were a series of Confirmatory Factor analyses. The results indicate an adequate reliability, and a strong invariance of the SCOP held across the two Spanish-speaking countries studied. SCOP is a valid instrument for intercultural comparisons between these groups, and it offers indirect evidence for comparisons with other Spanish-speaking countries of the same cultural background. This results may aid to design better interventions.